PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAM GAME TOURNAMENT) TERHADAP HASIL BELAJAR SISWA KELAS VII PADA MATERI FOTOSINTESIS DI SMPN 31 BATAM - Destaria Sudirman; Fenny Agustina; Pikal Candra (Universitas Riau Kepulauan, 2014)
This study aims to determine the type of use of Cooperative Learning Model (TGT) Team Tournament Game Against Student Results. This study is arandomized experiment with design Posttest Only Control Group Design with class VII entirepopulation. The sample in this study is the number of students VIIF class 30as aclass VIID experimental class and the number of students as a control group of 30 people. Sampling using a simple random sample (random sampling), data analysis techniques using ttest. Based on test data analysis instrument of 40 multiple choice questions about the 32 validated, while the reliability test is high (0.80 to 1.00). Test data results are normal prerequisites of FF table (1.029 1, 860) and homogeneity homogeneous L hitung L table (0.138 0.161), with an average value of 83 experimental class and the average value of the control class 68 shows the hypothesis test resultst (6,89)t table α of 5%(1.70). So that Ha=μ1 ≠ μ2 received whileHo=μ1=μ2 cancel, there are differences TGT cooperative learning model with the lecture method to the learning outcomes of students of class VII in photosynthetic material. Keywords: Cooperative Learning Model, Type TGT (Team Game Tournament), the Results learning outcomes